ROLE OF THINKING ON TEACHING COMPETENCY - PRE SERVICE TEACHERS PERSPECTIVE - N.Sasikumar,; Fathima, M.Parimala; Roja, M.Panimalar (Innovare Journal of Education, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> The teacher competence includes a thorough knowledge of the content.A teacher competence mainly includes the strategies, understanding of student psychology and the process of thinking.With regard to the former, plenty of resource material is available.But, the latter has been a continuous experimentation throughout the world. Cognitive Psychology contributes substantially in enhancing teaching competence.In recent times, cognitive neuroscience researches have demanded the teaching competence to be redefined to meet the challenges.Naturally, the learning process depends on the effective functioning of the brain. Thinking refers to the process of thought. To consider, judge or believe. The process of exercising the mind in order to make a decision, to remember or recollect, to make the mental choice between options.A focus on the development of thinking competencies within specific areas of the curriculum and across it not only serves as a core integrative function, it also has the potential to provide continuity in approaches to learning ,the view that such knowledge, skills and behaviours are important to lifelong learning. To emphasis' this, teachers model skilful and , and make their own thinking explicit as part of their everyday practice.The impact of thinking on class room activities and other educational activities is more to enhancing the teaching competency. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->